Persisting adverse body composition changes 2 years after cessation of androgen deprivation therapy for localised prostate cancer. Issue 1 (July 2018) - Cheung, Ada S; Tinson, Alistair J; Milevski, Stefan V; Hoermann, Rudolf; Zajac, Jeffrey D; Grossmann, Mathis
Abstract : Objective: Hypogonadism from androgen deprivation therapy (ADT) for prostate cancer causes adverse body composition changes associated with insulin resistance and decreased quality of life (QoL). Our objective was to assess whether adverse body composition changes improve after cessation of ADT. Design: Prospective case–control study in a tertiary referral hospital. Thirty-four men newly commencing ADT (cases, median age: 67.6 years (interquartile range: 64.6–72.0)) and 29 age-matched (70.6 years (65.3–72.9)) prostate cancer controls not on ADT were assessed 2 years after cessation of ADT (median: 4.4 years). Methods: Serum testosterone, body composition, handgrip strength, frailty and QoL were measured. Using a mixed model, the mean adjusted differences (MADs (95% CI)) between groups from baseline to study end are reported. Results: Twenty-seven cases and 19 controls completed the study. Median duration of ADT was 2.3 years (interquartile range: 1.8–3.1). Two years after cessation of ADT, total testosterone remained lower (MAD: −3.4 nmol/L (−6.3 to −0.5), P  < 0.022), fat mass (2214 g (490–3933), P  = 0.025) and insulin resistance (homeostasis model assessment of insulin resistance: 0.69 (0.31–1.07), P  < 0.001) remained higher in cases, whereas lean mass (−1450 g (−2259 to −640), P  < 0.001) and physical component of QoL remained lower than controls (−11.9 (−16.4 to −7.4), P  < 0.001). Conclusion: Two years after ADT cessation, metabolically adverse changes in body composition, increased insulin resistance and reduced QoL persisted. This may be related to incomplete testosterone recovery. Persisting adverse effects need to be considered in the risk to benefit assessment of ADT and proactive mitigation should continue after cessation of treatment.